Multilayer hybrid solid-state electrolyte membrane for the high rate and long-life cycle performance of lithium-metal batteries - Nassir, Wollela Behja; Mengesha, Tadesu Hailu; Chang, Jengkuei; Jose, Rajan; Yang, Chunchen (Elsevier B.V., 2024)
Hybrid solid-state electrolytes (HSEs) can be used to increase the electrochemical performance of lithium-metal batteries (LMBs), while also suppressing dendrite formation and preventing flammable behavior and electrolyte leakage, which are frequently present in conventional organic-liquid electrolytes. Notably, multilayer HSE membranes have received increasing emphasis since they can significantly ameliorate the interface contact toward electrodes and the mechanical strength. In this current work, we fabricated multilayer HSE membranes via a solution-casting technique that incorporated poly(vinylidene fluoride–co–hexafluoropropylene) (PVDF-HFP), polydopamine-modified Li6.28La3Zr2Al0.24O12 (PDA@LLZAO) filler, succinonitrile (SN) and lithium bis(trifluoromethane sulfonyl)imide (LiTFSI). The resulting HSE membrane exhibited a high ionic conductivity (2.49 ×10−4 S cm−1 at 30 ℃), transference number of 0.65, and excellent electrochemical window (4.80 V). The symmetrical cell featuring Li/HSE/Li was stable and cycled without short circuiting for 1000 h during the Li plating/stripping cycles. Furthermore, the coin-type cell assembled with LiFePO4/HSE/Li showed an initial discharge capacity of 134.7 mAh g–1 and exhibited superior retained capacity and average coulombic efficiency of 93.45% and 99.39%, respectively, after 687 cycles at 2 C and 30 ℃. Therefore, the as-prepared multilayer HSE is a promising SSE for next-generation LMBs.